Presence and Persistence of Coxiella burnetii in the Environments of Goat Farms Associated with a Q Fever Outbreak - Kersh, Gilbert J. (American Society for Microbiology, 2013)
Q fever is a zoonotic disease caused by inhalation of the bacterium Coxiella burnetii. Ruminant livestock are common reservoirs for C. burnetii, and bacteria present in aerosols derived from the waste of infected animals can infect humans. The significance of infection from material deposited in the environment versus transmission directly from infected animals is not known. In 2011, an outbreak of Q fever cases on farms in Washington and Montana was associated with infected goats. A study was undertaken to investigate the quantity and spatial distribution of C. burnetii in the environment of these goat farms. Soil, vacuum, and sponge samples collected on seven farms epidemiologically linked to the outbreak were tested for the presence of C. burnetii DNA by quantitative PCR. Overall, 70.1% of the samples were positive for C. burnetii. All farms had positive samples, but the quantity of C. burnetii varied widely between samples and between farms. High quantities of C. burnetii DNA were in goat housing/birthing areas, and only small quantities were found in samples collected more than 50 m from these areas. Follow-up sampling at one of the farms 1 year after the outbreak found small quantities of C. burnetii DNA in air samples and large quantities of C. burnetii persisting in soil and vacuum samples. The results suggest that the highest concentrations of environmental C. burnetii are found in goat birthing areas and that contamination of other areas is mostly associated with human movement.